Kepribadian dan Self - Regulated Learning - Asina Christina Rosito (Faculty of Psychology, Universitas Gadjah Mada, 2018)
There were few studies in Indonesia that had investigated the importance of personality in learning. This hypothesis of this study was there would be significance effect of the dimensions of personality based on Big Five Personality Traits Model on self-regulated learning. This study involved 342 college students. The instrument used were Big Five Personality scale and self-regulated learning scale. The result showed that 28,9% were categorized in extraversion type, 19% were categorized in conscientiousness, 17,5% in agreeableness and 14.9% were categorized in openness. Analysis of regression showed that there is significant effect of personality on self-regulated learning (R= 0,627; R2 = 39,3%; F= 43,43; p-value <0,001). Further analysis showed that between five dimensions of personality, only conscienstiousness and openness that have spesific contribution on self-regulated learning. It is important then to explore the most effective strategy to improve personal characteristics such as eager to learn new things, work hard and discipline Abstrak. Kajian tentang dinamika kepribadian sebagai salah satu faktor yang memengaruhi perilaku belajar masih relatif minim dilakukan di Indonesia. Hipotesis yang diuji dalam penelitian ini adalah dimensi-dimensi kepribadian berdasarkan model Big Five Personality Traits dapat memprediksi self-regulated learning. Partisipan penelitian berjumlah 342 mahasiswa Universitas HKBP Nommensen. Teknik pengumpulan data menggunakan skala Big Five Personality dan skala self-regulated learning. Hasil analisis menunjukkan bahwa tipe neuroticsm mendominasi dimana ada 99 orang (28,9%) tergolong tipe ini, disusul dengan extraversion sebanyak 67 orang (19,6%). Selanjutnya, terdapat 65 orang (19,0%) dengan tipe kepribadian conscientiousness, 60 orang (17,5%) dengan tipe kepribadianagreeableness, dan yang paling sedikit adalah tipe kepribadian openness yaitu 51 orang (14.9%). Analisis regresi menunjukkan bahwa tipe kepribadian Big Five Personality Traits ini dapat memprediksi secara signifikan terhadap self-regulated learning (R= 0,627; R2 = 39,3%; F= 43,43; p-value <0,001) secara khusus untuk dimensi kepribadian conscienstiousness dan openness.